Vaginal Cuff Dehiscence after Hysterectomy and One Minute Technique of Laparoscopic Vault Closure - Karki, Gyanendra Man Singh; Neupane, BB; Regmi, MC; Shrestha, R; Gupta, SN (Nepal Journal of Obstetrics and Gynaecology, 2017)
Aims: This study was done to observe the rate of vaginal cuff dehiscence of one minute technique of laparoscopic vault closure in laparoscopic hysterectomy. Methods: It was a descriptive study performed in Birat Hospital among 1012 patients undergoing total laparoscopic hysterectomy for both benign and malignant gynaecological conditions between 2012 to 2013. Monopolar cautery was used for laparoscopic colpotomy and vault was closed by laparoscopic single running suture, that is, one-minute laparoscopic vault closure technique. Patients were followed up for vaginal cuff dehiscence and the dehiscence rate was compared with other techniques of laparoscopic vault closure in laparoscopic hysterectomy. Results: This study showed that the rate of vaginal cuff dehiscence after one minute technique of laparoscopic vault closure in laparoscopic hysterectomy was 1/1012 patients (0.09%) which was significantly less as compared to other techniques of laparoscopic vault closure in laparoscopic hysterectomy quoted in the literature. Conclusions: One minute technique of laparoscopic vault closure after colpotomy with monopolar cautery using single running suture has encouraging results. It is a noble technique of laparoscopic vault closure with excellent support. It can be practiced in low resource setting also.